Enhancing Strength, Leg Muscle Explosive Power, and Muscle Hypertrophy Using Hurdle-Box Jump Plyometric - Permana, Dwinda Abi; Kusnanik, Nining Widyah; Nurhasan, Nurhasan; Setijono, Hari; Arifin, Muhammad Zainal; Purwoto, Septyaningrum Putri (Teorìâ ta metodika fìzičnogo vihovannâ, 2022)
The study purpose was to examine and analyze the effect of developing a hurdle-box jump plyometric model on muscle strength, explosive power, and hypertrophy. Materials and methods. This research was an experimental study with a two group pretest-posttest design. The sample in this study was male sub-elite athletes from various sports aged 15-17 years who were selected at random sampling totaling 22 athletes, divided into 2 (two) groups, the treatment group using plyometric hurdle-box jump development (n = 11) and the control group using plyometric barrier hops (n = 11). Results. The results showed that: (1) there was a significant effect of plyometric hurdle-box jump exercise on strength, leg muscle explosive power, and muscle hypertrophy, (2) there was a significant effect of plyometric barrier hops exercise (control group) on strength, leg muscles explosive power, and muscle hypertrophy, and (3) there was a significant difference between plyometric hurdle-box jump exercises and plyometric barrier hops exercises (control group) on strength, leg muscle explosive power, and muscle hypertrophy. Conclusions. The percentage increase in pretest and posttest scores on strength, leg muscle explosive power, and muscle hypertrophy showed that the hurdle-box jump plyometric exercise group was better than the control group (barrier hops).